2014
DOI: 10.1016/j.neuron.2014.07.041
|View full text |Cite|
|
Sign up to set email alerts
|

Discovery of a Biomarker and Lead Small Molecules to Target r(GGGGCC)-Associated Defects in c9FTD/ALS

Abstract: Summary A repeat expansion in C9ORF72 causes frontotemporal dementia and amyotrophic lateral sclerosis (c9FTD/ALS). RNA of the expanded repeat (r(GGGGCC)exp) forms nuclear foci or undergoes repeat-associated non-ATG (RAN) translation producing “c9RAN proteins”. Since neutralizing r(GGGGCC)exp could inhibit these potentially toxic events, we sought to identify small molecule binders of r(GGGGCC)exp. Chemical and enzymatic probing of r(GGGGCC)8 indicate it adopts a hairpin structure in equilibrium with a quadrup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
347
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 313 publications
(360 citation statements)
references
References 23 publications
13
347
0
Order By: Relevance
“…We showed that CSF poly(GP) has high power to differentiate C9orf72 expansion carriers and noncarriers, consistent with previous reports 10, 11, 14. Interestingly, poly(GP) levels were undetectable in three C9orf72 expansion carriers, who had various clinical presentations, including a presymptomatic individual, a bvFTD patient, and a PPA patient.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We showed that CSF poly(GP) has high power to differentiate C9orf72 expansion carriers and noncarriers, consistent with previous reports 10, 11, 14. Interestingly, poly(GP) levels were undetectable in three C9orf72 expansion carriers, who had various clinical presentations, including a presymptomatic individual, a bvFTD patient, and a PPA patient.…”
Section: Discussionsupporting
confidence: 91%
“…Disease‐modifying therapies advancing toward clinical trials include antisense oligonucleotides (ASOs) and small molecules that target G 4 C 2 transcripts and consequently reduce G 4 C 2 RNA foci and DPR proteins in C9orf72 patient‐derived cell models and animal models 9, 10, 11, 12, 13. In parallel with the rapid development of these potential therapeutics, biomarkers that measure target engagement, disease onset, and disease progression must be established for clinical trials to be successful.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkable advances have already been achieved in this direction, and they are presented in detail in this review. Briefly, antisense oligonucleotides/RNA interference sequences have been used to stimulate the elimination of pathological C9ORF72 transcripts [16,21,22] and the small compounds that are able to link the secondary structure of the repeat sequence, which can thereby limit the accumulation of RNA foci and toxic DPRs [23]. Indeed, short hairpin (sh) RNA or similar nucleotidic sequences, either naked or delivered with a viral vector, can be used for the same purpose.…”
Section: Introductionmentioning
confidence: 99%
“…Assays for the abundance of the disease-associated dipeptides could be used in a clinical trial setting to monitor the efficacy of potential disease-modifying therapies that target the repeat RNA expansion. These approaches could include small molecules, as shown by Su et al (10), and antisense oligonucleotides (6,11,12). More focus on understanding the molecular mechanisms of RAN translation could reveal new and unexpected therapeutic strategies.…”
mentioning
confidence: 99%